ANALYSIS OF THE TEMPERATURE PROPOSED BY THE INTERNATIONAL CONFERENCE OF HARMONIZATION (ICH) FOR COLOMBIA IN THE LONG TERM STABILITY STUDIES OF DRUGS - FLOREZ A., Oscar A.; ROJAS C., Jhon J.; GALLARDO C., Cecilia (Vitae, 2009)
The Mean Kinetic Temperature (MKT) concept is used to determine the storage and long term stability conditions of drug products in Colombia. It is considered that the value of 30°C fixed by I.C.H to our country should be reevaluated because of its climate conditions variability. Initially, to calculate the MKT, equations proposed by different authors are taken and applied to temperature data of Medellín. Subsequently, the MKT values for other five representative cities of the several climatic conditions of the country (Barranquilla, Barrancabermeja, Bogotá, Neiva y Quibdo) are found by using the average, maximum and minimum temperature values reported monthly during the last 20 years in meteorological stations. Finally, the results are compared with those published in the ICH guideline. As a conclusion of this work, our country should fix its own storage conditions, because 30°C is insufficient to give a security margin that covers completely the extreme temperatures of all the national territory.